2021
DOI: 10.1007/s41297-021-00140-w
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for social justice in the curriculum and pedagogical practices in higher education institution spaces in South Africa

Abstract: This study identified opportunities for social justice through inclusion in the curriculum and pedagogical practices in higher institution spaces in South Africa. A systematic review was done of past scientific studies carried out in South Africa that focused on social justice in the higher education curriculum and pedagogy delivery. Findings established that opportunities were available in higher education institutions' spaces for the elimination of injustice and inequality. Effective utilisation of these opp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Furthermore, the results of this study indicated that while some science teachers recognize the value of indigenous knowledge systems in science education, others may not be as familiar or as interested in the topic. This is consistent with previous research, which has shown that many science teachers may not recognize IKS' relevance to science education (Lawrence & Maphalala, 2021;Zidny et al, 2020). However, there is a growing body of literature that highlights the importance of incorporating IKS into science education (Kovach, 2021;Kugara et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, the results of this study indicated that while some science teachers recognize the value of indigenous knowledge systems in science education, others may not be as familiar or as interested in the topic. This is consistent with previous research, which has shown that many science teachers may not recognize IKS' relevance to science education (Lawrence & Maphalala, 2021;Zidny et al, 2020). However, there is a growing body of literature that highlights the importance of incorporating IKS into science education (Kovach, 2021;Kugara et al, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, to other countries such as Zimbabwe (Vongai & Elaosi, 2017), the South African curriculum mandates the inclusion of Indigenous Knowledge System (IKS) in science classrooms (Department of Basic Education, 2011). The literature demonstrates how STEM education and the indigenization of science practices in the classroom can support global goals for STEM education in Africa (Lawrence & Maphalala, 2021;McKinley, 2005). As envisioned, teachers are challenged by this agenda for curriculum reform.…”
Section: Introductionmentioning
confidence: 99%
“…Nowhere is this more apparent than in education, where disadvantaged youth are not equipped with the skills they need to succeed in life. The challenge for educators at institutions of higher learning is to alleviate these inequalities as an essential foundation of pedagogies of care in order to turn our society around (Lawrence & Maphalala, 2021).…”
Section: Introductionmentioning
confidence: 99%